2015
DOI: 10.2139/ssrn.2581311
|View full text |Cite
|
Sign up to set email alerts
|

Severe Air Pollution and Labor Productivity

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 36 publications
(24 reference statements)
3
33
0
Order By: Relevance
“…Even moderate concentrations of particulate matter commonly experienced in developed countries negatively affect the productivity of a selective group of professional soccer players, young and male athletes, to a considerable extent. Our findings hence complement previous empirical evidence on air pollution's negative effects on the productivity of low-skilled agricultural and factory workers in countries with higher levels of pollution (Graff Zivin and Neidell, 2012;Chang et al, 2014;Li et al, 2015). While our data allows us to consistently measure individuals' productivity for an entire industry and over multiple years, it remains unclear to what extent our findings can be generalized to the wider labor force.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Even moderate concentrations of particulate matter commonly experienced in developed countries negatively affect the productivity of a selective group of professional soccer players, young and male athletes, to a considerable extent. Our findings hence complement previous empirical evidence on air pollution's negative effects on the productivity of low-skilled agricultural and factory workers in countries with higher levels of pollution (Graff Zivin and Neidell, 2012;Chang et al, 2014;Li et al, 2015). While our data allows us to consistently measure individuals' productivity for an entire industry and over multiple years, it remains unclear to what extent our findings can be generalized to the wider labor force.…”
Section: Discussionsupporting
confidence: 73%
“…2 However, negative consequences of environmental damage are not limited to population health, with air pollution impacting the formation of human capital by affecting absenteeism, schooling outcomes or labor supply 3 , and hence triggering long-term consequences for individual earnings (Isen et al, 2014;Lavy et al, 2014a,b). Moreover, recent studies, provide evidence that pollution may also reduce workers' short-run productivity and thus hinder economic growth (Graff Zivin and Neidell, 2012;Chang et al, 2014;Li et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Existing evidence suggests that air pollution has negative effects on human health, especially for children and elderly adults. 1 A recent literature has also started to document negative effects among healthy adults in the form of reduction of labor productivity (Graff-Zivin and Neidell, 2012;Adhvaryu et al, 2014;Chang et al, 2014;Li et al, 2015) and hours worked (Hanna and Oliva, 2015). 2 These findings, from the U.S., India, and Mexico, point to changes in labor outcomes as relevant pollution externalities.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies focus on NOx (Deschenes et al, 2012), SO2 (Hanna and Oliva, 2015) and aerosols (Jayachandran, 2009). Among the few studies focusing on PM2.5 are Zweig et al (2014), Chang et al (2014), Adhvaryu et al (2014), Lavy et al (forthcoming) and Li et al (2015).…”
Section: Introductionmentioning
confidence: 99%
“…PM 2.5 has been found to lower the output of manufacturing workers in the Hebei province of northern China [11]. The authors obtained detailed productivity data from two firms and performed a similar analysis to the previously mentioned studies, and found productivity effects from exposure over a 30-day period.…”
Section: Additional Evidencementioning
confidence: 62%